Development Of Numbers Pyramid Media For Developing Cognitive Aspects Of Children Aged 5-6 Years - Rohyana Fitriani; Nopianti Nopianti; Zuhut Ramdani (Early Childhood Education Development and Studies (ECEDS), 2021)
The purpose of this research is to develop learning media in the form of a pyramid of numbers to develop the cognitive aspects of children aged 5-6 years. The development model used is Borg and Gall which consists of six stages. Products developed will be validated by a team of experts. The small scale subjects are 5 children and the large scale subjects are 15 children. The instrument used to collect data is an observation sheet. The results showed that the validation results of material experts obtained a score of 24 with an average value of 3.4 in the "good" category, the results of the media expert validation obtained a score of 31 with an average value of 3.8 in the "good" category. The results of the observations obtained that the percentage of pretest success was 46% (MB) and posttest 80% (BSB) and the results of hypothesis testing between pretest and posttest using the t-test was 1 < 2,048. From these results, it can be concluded that the number pyramid learning media is feasible to use to develop the cognitive aspects of children aged 5-6 years.